A Randomized Open Label Comparison of the Effects ofRisperidone and Haloperidol on Sexual Function - S. Jaber Mousavi; Mahyar Azar; Mona Ershadi; Narges Beyraghi (Iranian Journal of Psychiatry, 2009)
"n Objective: "nSexual dysfunction in patients who take antipsychotics causes adecline in their quality of life and medication acceptance. Considering the restrictions in cross sectional design of many earlier researches, we used a clinical trial aimed at assessing sexual dysfunction by substituting Risperidone, an atypical antipsychotic drug, with Haloperidol, a typical one . "n "n "nMethod: This clinical trial was conducted on 51 patients who had been using Risperidone with a minimum dose of 2 mg/daily for at least 2 months. The patients were randomly divided into 2 groups. The first group continued taking Risperidone, whereas the second group was given Haloperidol. Sexual function prior to and after the drug substitution was assessed using a sexual questionnaire designed to assess four stages of sexual function . "nResults: Compared to those who changed their medication to Haloperidol, the patients who remained on Risperidone therapy suffered from more sexual dysfunction, especially in their tendency towards having sexual activities (P= 0.01), post menstrual sexual activity (P= 0.002), and reaching orgasm in their sexual activities (P= 0.04); however in the Haloperidol group, no significant difference was observed before and after the change in medication . "nConclusion: Although Risperidone and Haloperidol can both disturb patients'sexual function, the side effects of Risperidone are stronger. Hence toprevent the decline of medication acceptance or irregular consumption by patients which may lead to possible relapse, substitution of Risperidone withanother drug with fewer side effects on sexual activities is definitely to the advantage of the patients .